2015
DOI: 10.1016/j.wneu.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of High Cervical Fractional Anisotropy in Acute Cervical Spinal Cord Injury

Abstract: Objective: Fractional anisotropy (FA) of the high cervical cord (C1-C2), rostral to the injury site, correlates with upper limb function in patients with chronic cervical spinal cord injury (SCI). In acute cervical SCI, this relationship has not been investigated. The objective of this study was to identify functional correlates of FA of the high cervical cord in a series of patients with acute cervical SCI. Methods: Traumatic cervical SCI patients who underwent presurgical cervical spine diffusion tensor imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…Animal studies of experimental spinal cord injury have shown an early decrease in FA after the injury [15]. Human studies in acute spinal cord injury have also described a significant decrease in FA in early spinal cord DTI after the injury [8, 16]. In the present study, changes in FA were sensitive to the number of ablations performed during the procedure.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Animal studies of experimental spinal cord injury have shown an early decrease in FA after the injury [15]. Human studies in acute spinal cord injury have also described a significant decrease in FA in early spinal cord DTI after the injury [8, 16]. In the present study, changes in FA were sensitive to the number of ablations performed during the procedure.…”
Section: Discussionsupporting
confidence: 50%
“…DTI is able to characterize microstructural changes within neural tissues, such as the spinal cord, and has been used to assess spinal cord lesions after spinal cord injury [7, 8] as well as microstructural changes in patients with cervical spondylotic myelopathy [9, 10]. To date, the role of DTI in characterizing the lesion produced by cordotomy has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…This region is also potentially useful for the prediction of outcomes in acute SCI, with a postoperative scan in the days to weeks following early surgical decompression. 38 The caudal region consistently showed the weakest results, likely due to respiratory motion, susceptibility artifacts from the lungs, and increased partial volume effects due to the angle between sections and the SC (in subjects with irreducible cervical lordosis). Despite these issues, T2*WI WM/GM and FA showed some utility in this region.…”
Section: Roismentioning
confidence: 94%
“…7 It was encouraging to also find strong results rostrally for T2*WI WM/GM, which has been previously reported for FA. 14,38 This finding has important clinical implications because this region avoids the aforementioned issues and can be used for postoperative assessment rostral to metallic implants in most patients with DCM. This region is also potentially useful for the prediction of outcomes in acute SCI, with a postoperative scan in the days to weeks following early surgical decompression.…”
Section: Roismentioning
confidence: 96%
“…Therefore it is not surprising that, in recent years, much effort has focused on imaging of traumatic SCI . Diffusion MRI in general and DTI in particular have been extensively used to study traumatic SCI both ex vivo and in vivo in experimental models and also in human subjects . Early work focused more on ex vivo diffusion MRI studies of traumatic SCI, but more recently in vivo studies have been conducted.…”
Section: Applications Of Diffusion Mri For Studying Sc Microstructurementioning
confidence: 99%